The Written Memory of St. Mary’s University College, Dublin (1893–1912): The Pioneer College for the Higher Education of Catholic Women in Ireland - Cunningham, John M. (Archivaria, 2019)
St. Mary’s University College, 28 Merrion Square, Dublin, was the first establishment in Ireland to provide for the university education of Catholic women, and its records testify to a revolution in female education. Originally generated to support its foundation and function, these records now provide information on the administration, actions, and achievements of this institution established in the 19th century by the Dominican Sisters of Eccles Street, Dublin. Both the University Education (Ireland) Act, 1879 and the Irish Universities Act, 1908 provide the fundamental context of their creation and original function. Although not all items are afforded consideration, this survey provides a sense of the variety and extent of the records preserved, discusses the motivations that favoured their preservation, and asserts that the records demonstrate an archival sensibility ahead of written norms and obligations. The records that now survive provide authoritative evidence of the manner and means of the foundation of St. Mary’s and of its purpose, character, context, and demise. RÉSUMÉ St. Mary’s University College, 28 Merrion Square, Dublin, a été le premier établissement en Irlande à fournir une éducation universitaire aux femmes catholiques et ses documents témoignent d’une révolution en matière d’éducation des femmes. Générés d’abord afin d’appuyer son établissement et ses fonctions, ces documents fournissent maintenant de l’information sur l’administration, les actions et les accomplissements de cette institution mise sur pied au XIXe siècle par les soeurs dominicaines d’Eccles Street à Dublin. La University Education (Ireland) Act, 1879 et la Irish Universities Act, 1908 offrent toutes deux le contexte fondamental de leur création et de leur fonction initiale. Bien que chaque item ne soit pas abordé, ce recensement offre une idée de la variété et de l’étendue des dossiers conservés, élabore sur les motivations derrière leur conservation et avance que les dossiers témoignent d’une sensibilité archivistique qui dépasse les obligations et les normes écrites. Les documents qui sont survécu fournissent un témoignage fiable de la façon dont St. Mary’s a été fondée, de sa mission, ses caractéristiques, son contexte et sa disparition.